MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK - Alfarizi . (Jurnal Edukasi dan Penelitian Matematika, 2021)
Problem solving ability is an ability that must be possessed by students in mathematics lessons. However in reality, students' mathematical problem solving abilities are still relatively low. To overcome this problem, the learning process can use Discovery Learning. This study aims to examine theoretically how the Discovery Learning model can improve students' mathematical problem solving abilities. The research was literature study methods and the sourced from secondary sources. This research was conducted by collecting and analyzing sources to obtain ideas about Discovery Learning and students' mathematical problem solving abilities. Based on the study conducted, it was found that theoretically the Discovery Learning learning model can improve students' mathematical problem solving abilities. The application of the learning stages of Discovery Learning can support student learning activities so that it can help improve students' mathematical problem solving abilities which can be seen from the achievement of mathematical problem solving indicators. Keywords –Discovery Learning, Mathematical problem solving ability